On algebraic degrees of certain exponential sums over finite fields - Lin, Xin (Forum mathematicum, 2025)
From a complex perspective, Birch and Bombieri (1985) proposed the study of an important class of -dimensional exponential sums for , which was then generalized by Katz (1987) to general positive integer . Our previous paper (2022) enhanced the preceding work from a complex point of view and expanded the subject to a -adic point of view for any positive integer . In this paper, we investigate the algebraic degree of the above exponential sum as an algebraic integer.